Pengaruh Citra Merek (Brand Image) Terhadap Keputusan Pembelian Kerudung Deenay (Studi pada Konsumen Gea Fashion Banjar) - Iis Miati (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
The development of the economy at this time will cause very tight competition in the business field. The company will continue to develop its products by creating unique products that are different from competitors that produce similar products. At this time consumers are fanatic in choosing a product, besides they want a quality product they will also choose a product that has a brand image that is quite good in the community. Deenay veil products are currently a product that is favored by every society. At Gea Fashion Banjar deenay brand hood sales are higher each month compared to other brand hoods. Based on that, the writer is interested in researching the Effect of Brand Image on the Decision to Purchase Deenay Veil in Banjar Gea Fashion. The purpose of this study was to determine how the influence of Brand Image on the Purchase Decision Deenay Veil on Banjar Gea Fashion? The research method used is quantitative descriptive research method, with a sample of 50 people. The results showed that brand image had a significant influence on the decision making for purchasing veil deenay. This significance value was obtained from Fcount 29,689 with a significance of 0,000 with F table (4.04) at the significance level of 0.05 and the coefficient of determination (r²) or R square obtained by 0.328, so that the magnitude of influence was 38.2%, whereas the remaining 61.8% is influenced by other factors not included in this research variable. In conclusion, consumers make purchasing decisions due to the influence of brand image and social, cultural, personal and psychological factors.